Busting Out: Predictive Brains, Embodied Minds, and the Puzzle of the Evidentiary Veil. (13th April 2016) - Clark, Andy
Abstract: Biological brains are increasingly cast as 'prediction machines': evolved organs whose core operating principle is to learn about the world by trying to predict their own patterns of sensory stimulation. This, some argue, should lead us to embrace a brain‐bound 'neurocentric' vision of the mind. The mind, such views suggest, consists entirely in the skull‐bound activity of the predictive brain. In this paper I reject the inference from predictive brains to skull‐bound minds. Predictive brains, I hope to show, can be apt participants in larger cognitive circuits. The path is thus cleared for a new synthesis in which predictive brains act as entry‐points for 'extended minds', and embodiment and action contribute constitutively to knowing contact with the world.